2021
DOI: 10.1187/cbe.20-05-0096
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model of Graduate Teaching Assistant Teacher Efficacy: How Do High and Low Teacher Efficacy Teaching Assistants Compare?

Abstract: This study identifies factors that influence the development of teacher efficacy in STEM graduate teaching assistants over the course of one semester. Those with high teacher efficacy draw upon mastery experience, vicarious experience, and verbal and social persuasions from reliable sources, such as professors and accomplished peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…We therefore expect that GTAs of CUREs who have less experience or support may therefore not experience the same high degree of self-efficacy as the GTAs in our study. While we expect this strong self-efficacy among the study participants to support their motivation to teach the CURE, recent work has found that GTA assessments of their own self-efficacy do not significantly correlate with student evaluations of their GTAs ( Smith and Delgado, 2021 ), indicating that students have differing perceptions of their GTAs’ efficacy in the classroom.…”
Section: Discussioncontrasting
confidence: 99%
“…We therefore expect that GTAs of CUREs who have less experience or support may therefore not experience the same high degree of self-efficacy as the GTAs in our study. While we expect this strong self-efficacy among the study participants to support their motivation to teach the CURE, recent work has found that GTA assessments of their own self-efficacy do not significantly correlate with student evaluations of their GTAs ( Smith and Delgado, 2021 ), indicating that students have differing perceptions of their GTAs’ efficacy in the classroom.…”
Section: Discussioncontrasting
confidence: 99%
“…Their findings suggest that an impediment to shifting to student-centered approaches was the students themselves, who pressured TAs to practice non-inquiry techniques by requesting more teacher-centered feedback. This finding is in agreement with the Smith and Delgado (2021) model, which shows how novice TAs’ beliefs and practices are susceptible to student influence, which may not reliably indicate effective instruction.…”
Section: Theoretical Framework and Background Literaturesupporting
confidence: 81%
“… Smith and Delgado (2021) developed a model of TA self-efficacy ( Figure 1 ) in an effort to advance the literature on TA PD by framing factors that improve the self-efficacy of TAs and how to shift their focus of concern beyond their own tasks to impacting student learning. The model is based on TA interview data that indicated the main sources of self-efficacy for high and low self-efficacy TAs.…”
Section: Theoretical Framework and Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the multivariate analysis, we found that previous TA work experience and future career expectations would affect TAs' con dence. The experience was regarded as a critical factor for the teacher e cacy of TA 14 . Previous teaching experience might signi cantly improve the self-e cacy of TA 15 .…”
Section: Discussionmentioning
confidence: 99%